Influence of water replacement on Diflubenzuron duration effect in the control of Aedes aegypti in simulated field conditions, in Northeastern Brazil - Garcia Neto, Levindo Jose; de Goes Cavalcanti, Luciano Pamplona; Pontes, Ricardo Jose Soares; Lima, José Wellington Oliveira (Journal of Health & Biological Sciences, 2013)